This I Believe - Killion, George L. (Tufts Archival Research Center, 2006)
George Killion remembers his father and the beliefs his farther imparted to him: compassion, respect for others, and adherence to the Golden Rule. George Killion remembers his father and the beliefs his farther imparted to him: compassion, respect for others, and adherence to the Golden Rule.